Ventilation Adjustment in ECT During COVID-19: Voluntary Hyperventilation is an Effective Strategy - de Arriba-Arnau A (Dove Medical Press, 2021)
Aida de Arriba-Arnau,1,2 Antònia Dalmau Llitjos,3 Virginia Soria,1,2,4 Javier Labad,2,5,6 José Manuel Menchón,1,2,4 Mikel Urretavizcaya1,2,4 1Department of Psychiatry, Bellvitge University Hospital-ICS, Bellvitge Biomedical Research Institute (IDIBELL), Neurosciences Group - Psychiatry and Mental Health. L’Hospitalet de Llobregat, Barcelona, Spain; 2Centro de Investigación Biomédica en Red de Salud Mental (CIBERSAM), Carlos III Health Institute, Barcelona, Spain; 3Department of Anesthesiology, Reanimation and Pain Clinic, Bellvitge University Hospital-ICS, Universitat de Barcelona (UB), Barcelona, Spain; 4Department of Clinical Sciences, School of Medicine, Universitat de Barcelona (UB), Barcelona, Spain; 5Department of Mental Health, Consorci Sanitari del Maresme, Mataró, Spain; 6Parc Taulí, Institut d’Investigació i Innovació Parc Taulí (I3PT), Barcelona, SpainCorrespondence: Mikel UrretavizcayaSarachaga Department of Psychiatry. Bellvitge University Hospital – ICS, IDIBELL, CIBERSAM; UB Feixa Llarga s/n, 08907, L’Hospitalet de Llobregat, Barcelona, SpainTel +34 932607922Fax +34 932607658Email murretavizcaya@bellvitgehospital.catPurpose: Airway management is a key objective in adapted electroconvulsive therapy (ECT) protocols during the COVID-19 pandemic to prevent infection. The objective of this study was to describe the effectiveness of a modified ventilation procedure designed to reduce aerosol-generating bag-mask ventilation (BMV) and isolate possible droplets while maintaining adequate respiratory gas values in ECT sessions.Materials and Methods: This prospective study analyzed the results of the modified protocol applied over a month. Adaptations entailed preoxygenation and extension of the voluntary hyperventilation (VHV) time for two minutes before anesthesia induction, asking patients to hyperventilate with oxygen therapy via nasal cannula and while wearing a face mask. Thereafter, vigorous hyperventilation was avoided, and patients were only assisted with tightly sealed BMV until emergence from anesthesia, isolating the ventilation by using a single-use plastic device. Oxygen saturation (SpO2) and transcutaneous partial pressure of carbon dioxide (TcPCO2) were recorded throughout the session.Results: The study included 74 sessions of bilateral ECT with the modified ventilation protocol in 15 subjects. After VHV, the mean SpO2 increase was 2.12± 2.14%, and the mean TcPCO2 decrease was 4.05± 2.98 mmHg. TcPCO2 values at the moment of stimulus administration were 2.22± 3.07 mmHg below pre-ECT values. The mean EEG seizure was 38.70± 17.03 s, and postictal suppression was 68.31± 34.58% and 2.13± 0.75 on a 0– 3 scale. Brief desaturation (SpO2 < 90) of 4– 5 seconds duration was observed in 4 sessions.Conclusion: This modified ventilation protocol was effective during COVID-19, and it did not elicit significant side effects. In addition to avoiding vigorous BMV, it induced moderate hypocapnia, which has been tied to seizure optimization and less hypercapnia during the apnea period.Keywords: electroconvulsive therapy anesthesia, ECT, airway, bag-mask ventilation, oxygenation, self-hyperventilation, hypocapnia